Application of a risk score model based on tyrosine-related genes in the prognosis and treatment of patients with lung adenocarcinoma - Wang, Huan; Li, Yuebei; Liu, Ke; Fan, Xinyuan (Frontiers in Immunology, 2025)
BackgroundTyrosine is associated with alterations in the tricarboxylic acid cycle in lung cancer, and exploring tyrosine-related genes (TRGs) has the potential to contribute to the construction of new sensitive prognostic biomarkers for patients with lung adenocarcinoma (LUAD).MethodLung cancer prognosis model was constructed by Lasso Cox regression, univariate and multivariate COX regression, GSEA, TIDE. Potential drugs were screened and drug sensitivities analyzed by the pRRophetic software package. And the role of MYO6 in lung cancer was confirmed by experiments in vitro.ResultsWe identified 7 TRG risk score models (ZFP3, MEAK7, MMUR1, GTF3C6, MYO6, MAPK1IP1L and VAX1) for the diagnosis and prognosis of patients with LUAD. ROC curves and the C-index suggested that the risk score had more reliable diagnostic significance and could more accurately predict the prognosis of LUAD patients. The nomogram model was constructed with risk scores, which can be used to predict an individual and visualize the correlation between the total score and the predicted outcome more intuitively. Additionally, it has an impact on immunotherapy efficacy, tumor mutation burden and drug sensitivity. In addition, high expression of myosin VI (MYO6) was related to tumor proliferation and metastasis in vitro.ConclusionIn conclusion, the risk scores constructed from seven TRGs have great potential for survival prognosis, immunotherapy response and drug sensitivity. MYO6 plays an oncogenic role in promoting proliferation and metastasis in patients with LUAD, which provides a new theoretical basis for the diagnosis and treatment of LUAD patients.